Qualidade tecnológica de grãos de feijão carioca armazenados - João, Esperança Cativa Baptista (2016)
Beans are leguminous plants, an important source of protein, minerals, complex carbohydrates, unsaturated fatty acids, dietary fibers and vitamin B. In Brazil it is grown in three crops: water crop, dry crop and autumn/winter crop. The bean classification is based on the framework of the product in group, class and type. The botanical species indicates the group, and the group I the Phaseolus vulgaris L. species (carioca) and Group II, the species Vigna unguiculata (L.) Walp (feijão-de-corda). The carioca commercial type beans are produced in three crops and has most national preference. These grains are characterized by rapid loss of quality during storage in uncontrolled conditions of temperature and relative humidity. These quality losses include dimming the integument, development defect of hard-to-cook texture and consequent increase in cooking time and less viscous broth production, which causes the grain to be rejected by consumers. This study was to evaluate the effect of storage at room temperature, the technological quality of five cultivars (BRS 9435 Cometa, BRS Estilo, BRSMG Majestoso, BRSMG Madrepérola e BRS Notável) of carioca bean, produced in the crop dry, in six storage times (60, 90, 120, 150, 180 and 210 days after harvest, or dac). It was considered a completely randomized design, with five cultivars and six storage times, in 5x6 factorial design with three replications. The grain moisture varies with the variation of the relative humidity of the storage environment. The beans grains of all varieties have darkening of integument during storage, however, the cultivar BRSMG Madrepérola have the lowest susceptibility to darkening, and the cultivars BRS 9435 Cometa, BRSMG Majestoso and BRS Notável are more susceptible of darkening. The beans with the shorter cooking during storage are the BRS 9435 Comet and more cooking time are the cultivars BRSMG Madrepérola and BRS Estilo. In principal component analysis, the variables average time of cooking (TMC), thickness of the integument (ET), percentage of whole grains after cooking (PGIAC), percentage of soaking before cooking (PEANC) and volumetric expansion rate (TEV) they are those that most influence the technological quality of the beans of the cultivars evaluated. How greater is the thickness of the integument, mainly represented by the lacunose parenchyma, greater is the PEANC in all cultivars. With higher the moisture and grain size, the smaller the TMC. The resistance to compressive force lowers with the increase of storage and increasing the cooking time, when grains are cooked by the cooking time determined by Mattson cooker, in all cultivars and increases when cooked for 20 minutes. The viscosity of the cooking broth and total solids increase with storage and increasing the cooking time, when grains are cooked by the time obtained by the Mattson cooker, for all cultivars and reduces when cooked for 20 minutes. The brightness of the cooking broth reduces in all cultivars with increased storage time, in two kinds of cooking. There is a positive correlation between the brightness of the seed coat and bean broth cooked for 20 minutes and the bean broth cooked for the cooking time determined by Mattson cooker.